(untitled) - Kalasova, Alica (Doprava a spoje, 2006)
IIn recent years we can notice a decrease in interest in city public transport.. That is why with ITS applications, we should try to make city public transport more attractive for general public. In my contribution I concentrated on tropical problems of personal public transport as preference and progressive information systems that I schematically described.